Impact of high temperature stress on photosynthetic characteristic and yield of rice (Oryza sativa) at heading - XIE, XIAO JIN; LI, BIN BAI; SHEN, SHUANG HE (The Indian Journal of Agricultural Sciences, 2012)
To estimate impact of high temperature stress on photosynthetic characteristic and yield in rice (Oryza sativa L.), a pot experiment was conducted during 2008 in environment-controlled chambers with two rice cultivars (Yangdao 6 and Nanjing 44) under high temperature stresses (35°C/3d, 35°C/5d, 39°C/3d and 39°C/5d) at heading. The results showed that rice grain yield, chlorophyll content, net photosynthetic rate (NPn), superoxide dismutase content (SOD) and leaf area index (LAI) presented a sharply decline, and the relative conductivity, malondialdehyde content (MDA) increased gradually with the elevation of stress temperature and extension of stress time. The increasing rate (reduction rate) of some physiological and biochemical indexes in Yangdao 6 were lower than that in Nanjing 44 compared with the CK under the same temperature stress. It was showed that response of Nanjing 44 to high temperature was stronger than that of Yangdao 6. In accordance with correlation analysis, the rice grain yield showed a positive correlation with NPn and LAI (P